Kantian Ethics And The Hesc Research: A Philosophical Exploration - Abakare, Chris O. (Program Studi Sosiologi, 2020)
The scientific reports on the successful use of Human Embryonic Stem cells to cure many sicknesses as provoked a long-standing controversy about the ethics of research involving human embryos. This controversy arises from sharply differing moral views regarding the use of embryos for research purposes. Indeed, an earnest international scholarly debate continues till today over the ethical, legal, and medical issues that arise in this arena. Immanuel Kant (1724-1804) had given a moral guideline that ethical decisions should be made by considering the nature of the act itself, not its consequences. Furthermore, Kant has warned that persons (autonomous agents) have a special moral worth or dignity, which is the basis for the respect that is owed to them. Thus, respect for persons, means never using persons merely as means to our ends, but always treating them also as ends in themselves. Some philosophers like Richard Doerflinger, Michael Novak, Gilbert Meilaender, and Robert P. George have used the Kantian formula of humanity to criticize the argument that spare IVF embryos can be used for stem cell research given their inevitable death and thus lack of properties for future life. However, the purpose of this paper is to take a critical look at the Human Embryonic Stem cells subject matter to investigate the concept of “personhood’, with the maxim of ‘never treating a person as a means’. This paper argues that if we accepts the definition of a person to possess capacities such as ‘rational’ ‘will’ and ‘self-determination’, then IVF embryos is not a person and can therefore be researched upon, used to derive human embryonic stem cells. Hence, Human Embryonic Stem cells research can be carried out within the ambiance of Kant Categorical Imperative without moral conflict.